2010
DOI: 10.1002/mabi.200900248
|View full text |Cite
|
Sign up to set email alerts
|

On the Effects of UV‐C and pH on the Mechanical Behavior, Molecular Conformation and Cell Viability of Collagen‐Based Scaffold for Vascular Tissue Engineering

Abstract: Collagen-based vascular substitutes represent in VTE a valid alternative for the replacement of diseased small-calibre blood vessels. In this study, collagen gel-based scaffolds were crosslinked combining modulation of pH and UV-C radiation. The effects on the mechanical properties, on the molecular structure and on cell viability and morphology were investigated. The mechanical response increased as a function of pH or UV-C dose and strongly depended on the test speed. Collagen molecular conformation resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 57 publications
2
37
0
3
Order By: Relevance
“…The mechanical behavior was evaluated by considering the compressive modulus (CM), defined as the linear regression between 15 and 30% of strain, and the compressive strain energy (CSE), defined as the integral of the curve between 0 and 40% of strain. The gel prepared at pH 7, at an ionic strength corresponding to c4 and set at 37 °C was used as a control because, except for the concentration of collagen, it presented the same experimental conditions as the one previously studied in our laboratory [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical behavior was evaluated by considering the compressive modulus (CM), defined as the linear regression between 15 and 30% of strain, and the compressive strain energy (CSE), defined as the integral of the curve between 0 and 40% of strain. The gel prepared at pH 7, at an ionic strength corresponding to c4 and set at 37 °C was used as a control because, except for the concentration of collagen, it presented the same experimental conditions as the one previously studied in our laboratory [25].…”
Section: Methodsmentioning
confidence: 99%
“…This approach implies three experimental conditions: preparation of the gel solution with culture medium, gelation in the incubator and neutral pH [12,25]. These conditions fix the ionic strength, the pH and the temperature at which fibrillogenesis occurs and affect the size of the fibrils, the interactions between neighboring fibrils and, consequently, the type of microstructure and the mechanical properties of the scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many skin changes like easy bruising which were believed to be a result of aging, are in fact related to prolonged UV exposure (Sionkowska, ). In addition, the UV‐collagen interaction affects the cell response, since it has been reported that cells that were cultured on UV–irradiated collagen‐based materials are influenced by UV irradiation parameters (Rajan et al, ; Achilli et al, ). Hence, due to the chronic exposure of human skin to sun light the clarification of the UV‐collagen interaction mechanisms is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…As observed in Figure a1, FTIR analysis of collagen clearly exhibited the expected spectrum. Indeed, amide bands type I and II from collagen were at 1,656 and 1,554 cm −1 , respectively (Achilli, Lagueux, & Mantovani, ; Sionkowska et al, ). Based on the GNF structure, the characteristic bands from fluorocarbon chain were also detected (Figure a1), with a main band from CF 2 symmetric stretching at 1,201 cm −1 .…”
Section: Resultsmentioning
confidence: 99%